Panji Jayalengkara Angreni: Jalinan Kisah Panji dalam Sastra Tulis dan Kesenian (Sutasoma : Jurnal Sastra Jawa, 2023)
Panji Jayalengkara Angreni which is one part of the Panji Angreni variety has a close relationship with oral and written traditions. With the existence of multi-layered traditions and a very broad corpus, it is necessary to describe the distribution of traditions, especially in the realm of Javanese culture in Surakarta. Thus, this study aims to reveal the relationship between the oral and written traditions of Panji Jayalengkara Angreni. In revealing this relationship, it is necessary to understand that the manuscript and oral traditions are a unity as a basic foundation. This study uses a qualitative method and is based on a research method that combines manuscript writing traditions and artistic traditions, as was done by Vickers on the Malat text. As a limitation, the search for the corpus of written and oral literature is only focused on the Surakarta tradition, especially those related to oral literature in performing art. The text of Panji Angreni appears in the literary tradition of the northern coast of Java which developed with additions and recompositions. Panji Angreni Palembang as the oldest text shows the form of Panji Angreni which is still much influenced by Old Javanese literature. Panji Angreni developed by being combined with the story of Jayalengkara in the Surakarta era.The relationship between Panji Jayalengkara Angreni's written text and oral text is evident in the realm of wayang, dance, and musical performances. This relationship is not just a one-way relationship, but a reciprocal relationship between written and oral traditions. Keywords: Panji; oral tradition; written tradition; wayang.